Esther through the Centuries. By Jo Carruthers - De Troyer, Kristin (The journal of theological studies, 2011)
This volume is part of a series that attempts to present the reception history of biblical books and that focuses on ‘the influence of the Bible on literature, art, music and film, its role in the evolution of religious beliefs and practices, and its impact on social and political developments’ (editors’ preface, p. xiii). The volume under review is certainly a great step in ‘unearthing Esther’s reception’ (as the author puts it, p. 3)., The first 51 pages form an excellent introduction to the volume, covering what the author intends to do (‘The interpretations are not aimed as “pure registers” of their cultural and historical location, but approached as individual and uniquely motivated responses to this specific biblical text, grappling with its authority’, p.